Exploring the Role of Social Capital in Strengthening Community Bonds for Sustainable Development - Sari, Siti Annisa Nur Mirna; Ahmad, Makmur; Junaedi, Dandi (Journal Social Civilecial, 2024)
This paper seeks to identify and analyze the functions of social capital in community development namely through respect, exchange, mutual purpose and networks. A qualitative primary research technique in the form of case studies and questionnaires, administered on selected community heads and influential members, explore how these attributes of social capital build trust and cooperation to strengthen community management and development agenda. Aluthgama reveals that cultural commonalities, historical antecedents and emerged computer networks significantly support community-based associations and joint activities. The study also underscores the positive correlation between the official organizations and the relations-based networks, where a mix of the two is argued to be key for supporting sustained community-based practice. Further, the study highlights how appreciation for the initiation and creation of joint benefits among community members is related to technology, a topic that has been given limited attention in prior social capital scholarship. Thus, the findings of the current work bring to the scholarly discourse a more nuanced understanding of social capital regarding its relationship with community resilience and development. To policymakers and community leaders, it carries potential for improving both conventional and web/clique social capital inventory, noting that these findings have practical implications.